Artificial Intelligence for Business: A Conceptual Review - Chukwuma, Isaac Onyeyirichukwu; Alaefule, Fidelis Odinakachukwu; Madu, Ifeanyi Leo; Egbosionu, Anthonia Nneka; Okeke, Matthew Arinze; Chukwuma, Patrick Chukwunwike (International Journal of Scientific Research and Management (IJSRM), 2024)
This conceptual review examined the dynamics of artificial intelligence (AI) in the business landscape. As businesses traverse an increasingly complex industrial landscape, AI provides a strategic tool for improving effectiveness, innovation, and decision-making. This study aimed to examine and provide a comprehensive view of AI’s influence on business. This paper deployed a qualitative research approach; utilising a narrative literature review methodology to examine existing literature which provided a relevant comprehensive perspective of AI in businesses. The study specifically examined themes on the antecedents of AI for business, challenges of AI for business, dual role (necessity or advantage) of AI in organization operations, AI effect on business/organizational interest, and the resource-based view (RBV) theory perspective on AI for business. The study is of the position that businesses can position themselves for success in the rapidly evolving AI-driven environment by optimizing AI integration and deployment as a strategic approach to future market relevance.